Informal Settlement and Community Adaptation Along the Railway Road in Cimahi - Nabilla Dina Adharina; Silma Desvita Mayapada; Tia Adelia Suryani (Jurnal Teknik Sipil dan Perencanaan, 2024)
Due to urbanization, informal settlements have been portrayed as a form of adaptation in managing a community’slimitations. Using informal settlements along the railway road in Cimahi City as a case study and qualitative method, this study aims to see how the community conducts adaptation and shapes the surrounding environment. The study found two types of adaptation, adjustment and reaction, as a response to rail noises, limited space, and accident-prone problems. In addition to the adaptation, there is a co-production in producing services to assure the community’s safety since they live along the railway road. The findings revealed that the absence of government in guaranteeing citizens’ rights has enforced community creates a system that increases community resilience.